Sistem Pendukung Keputusan Pemberian Point Tambahan Perkuliahan Menggunakan Metode SMARTER - Triana Elizabeth; Tinaliah Tinaliah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Based on academic data, practicum courses are courses that are difficult for students to take. This can be seen from the number of students who repeat or get a final D or E in practicum courses compared to theory courses. The consequence of getting a final grade of D or E is that students are unable to graduate on time or even fail to graduate from college. Assessment is based on 5 components, namely: Quiz 10%, Assignment 10%, UTS 30%, UAS 30%, and Softskill 10%. Based on the weight of the proportion, UTS and UAS scores play an important role in whether a student can pass the course or not, and usually it is the UTS and UAS scores that make the entire final grade drop even though the scores of other components are high. One way to overcome this is to provide additional lecture points. The decision support system for awarding additional lecture points uses the SMARTER method and uses 5 criteria, namely the number of exercises carried out, liveliness, attitude during lectures and timeliness when submitting assignments can provide recommendations for additional lecture points more objective and more accurate.